2019
DOI: 10.1016/j.jhep.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

News in pathophysiology, definition and classification of hepatorenal syndrome: A step beyond the International Club of Ascites (ICA) consensus document

Abstract: Renal dysfunction is a common, life-threatening complication occurring in patients with liver disease. Hepatorenal syndrome (HRS) has been defined as a purely ''functional" type of renal failure that often occurs in patients with cirrhosis in the setting of marked abnormalities in arterial circulation, as well as overactivity of the endogenous vasoactive systems. 4,5 In 2007, the International Club of Ascites (ICA) classified HRS into types 1 and 2 (HRS-1 and HRS-2). 5 HRS-1 is characterised by a rapid deterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
299
2
30

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(374 citation statements)
references
References 100 publications
3
299
2
30
Order By: Relevance
“…Im Rahmen der bakteriellen Translokation kommt es außerdem zu einer vermehrten Expression von tubulären Toll-like-Rezeptoren in der Niere [37], die mit einem renalen Funktionsverlust durch Schädigung und Apoptose der tubulären Zellen einhergeht [65,66]. Der dafür verantwortliche pathophysiologische Mechanismus ist derzeit noch nicht bekannt.…”
Section: Theorie Der Chronischen Inflammationunclassified
See 2 more Smart Citations
“…Im Rahmen der bakteriellen Translokation kommt es außerdem zu einer vermehrten Expression von tubulären Toll-like-Rezeptoren in der Niere [37], die mit einem renalen Funktionsverlust durch Schädigung und Apoptose der tubulären Zellen einhergeht [65,66]. Der dafür verantwortliche pathophysiologische Mechanismus ist derzeit noch nicht bekannt.…”
Section: Theorie Der Chronischen Inflammationunclassified
“…Sowohl DAMPs als auch PAMPs aktivieren über verschiedene Signalkaskaden eine Verminderung des mitochondrialen Stoffwechsels der proximalen Tubuluszellen in der Niere, was wiederum zu einer verminderten Aufnahme von luminal lokalisiertem Natrium (Na) und Chlorid (Cl) führt. Eine dadurch bedingte Konzentrationssteigerung von NaCl im Bereich der Macula densa des juxtaglomerulären Apparats löst eine weitere intrarenale Aktivierung des RAAS und eine damit verbundene Abnahme der GFR aus [37].…”
Section: Theorie Der Chronischen Inflammationunclassified
See 1 more Smart Citation
“…HRS carries an extremely high mortality and has been thought to be mostly related to a decrease in renal perfusion in liver disease 47 but there is now evolving evidence that it may also be caused by systemic inflammatory changes, microvascular dysfunction, and direct tubular damage. 48 Brensing et al treated 31 nontransplantable patients with both type 1 and type 2 HRS and showed that renal function did improve after TIPS placement. 49 Guevara et al studied TIPS in patients with type 1 HRS, the most severe form of acute kidney injury in liver disease, and found a significant improvement in serum creatinine, blood urea nitrogen, GFR, and renal plasma flow.…”
Section: Renal Dysfunctionmentioning
confidence: 99%
“…Overall, current published data do not support the existence of a continuum between HRS and ATN as proposed in the review article. 1 While we cannot discount the possibility that a continuum does exist, confirmation of such a hypothesis would require performing 2 kidney biopsies, 1 at diagnosis of HRS-AKI and 1 during follow-up. However, current evidence does not provide a sufficiently solid background to warrant such a study.…”
mentioning
confidence: 98%